OP0202-PC Use of Over-the-Counter Non-Steroidal Anti-Inflammatory Drugs in the General Population and in Patients with a High Risk of Adverse Drug Events. (23rd January 2014) - Koffeman, A.; Valkhoff, V.; Çelik, S.; 't Jong, G.; Sturkenboom, M.; Bindels, P.; Van der Lei, J.; Luijsterburg, P.; Bierma-Zeinstra, S.
Abstract : Background: The use of non-steroidal anti-inflammatory drugs (NSAIDs) is associated with serious adverse drug events (ADEs) 1 . In many countries, including the Netherlands, NSAIDs are available over-the-counter (OTC). Objectives: To determine the prevalence of OTC NSAID use in the general population and in patients with a high risk of developing a serious NSAID-related ADE. Methods: We conducted a cross-sectional study among adults registered with four Dutch general practitioners (GPs). In the Netherlands, all citizens are registered with a GP. Two samples of different patient populations were selected: (i) a random sample of adults (general population), and (ii) a sample of adult patients with a high risk of developing a serious ADE in case of NSAID use (high-risk population). The patients' risk profiles were determined using their electronic medical records. Based on Dutch clinical prescription guidelines 1, patients were considered at high risk if they had a history of a peptic ulcer or ulcer complication, myocardial infarction, stroke or heart failure, were aged over 70 years, had a glomerular filtration rate < 30ml/L, or had a combination of two or more of the following: use of an anticoagulant, aspirin, corticosteroid or selective serotonin reuptake inhibitor; age 60-70 years; history of severe rheumatoid arthritis or diabetes mellitus. All included patients were sent a questionnaire regarding their use of OTC NSAIDs in the four weeks prior to participation. Results: In the general population, 120 of 456 included patients chose to participate. Of these, 35 (29%) had used an OTC NSAID in the four weeks prior to participation. In the high-risk population, 265 of 713 included patients chose to participate and 33 (13%) had used an OTC NSAID. Musculoskeletal complaints formed the most common reason for OTC NSAID use in the high-risk population, with 67% of OTC NSAID users giving this as a reason for use. In the general population, 46% of OTC NSAID users reported using these drugs because of musculoskeletal complaints. Over 20% of OTC NSAID users had used the OTC NSAID for more than seven days in the general population and over 30% in the high risk-population. OTC NSAIDs were used in a dosage exceeding the recommended daily maximum by 9% and 3% of OTC NSAID users in respectively the general and the high-risk population. Conclusions: OTC NSAIDs are used by around one third of the general population and by one in eight patients with a high risk of developing a serious ADE. In this high-risk group, musculoskeletal complaints form the most common reason for OTC NSAID use. Continued efforts by healthcare professionals to inform patients of the risks of these drugs is warranted, particularly when a new diagnosis is made or medication prescribed which alters the patient's risk profile. References: Warlé-Van Herwaarden MF, Kramers C, Sturkenboom MC, et al. Targeting outpatient drug safety: Recommendations of the Dutch Harm-Wrestling Task Force. Drug Saf 2012;35(3):245-59 Disclosure of Interest: None Declared